Um método estocástico de alocação de memória - Lerner, Jayme (1973)
We introduce the development of the theory of stochastic process as applied to paging systems, and at the end of the study we formulate a paging algorithm. First we borrow some properties of algebra, and with these results we develop the necessary theory to the mathematical interpretation of the chains of pages that link two given pages of the program in the computer. Then noticing randomnes as a main factor in the developed structure, we introduce some result that explain the law of formation of these chains. There after, we introduce the concepts of mean first passage time, mean absorption, time, and results we deem necessary to the studies natural evolution. We apply these results to a particular Markov chain namely the random walk in the circle, aiming to get informations about the chain formation laws for this particular case, results whereon we will be able to formulate a paging algorithm.